Sistem Solar Tracker Dual Axis Berbasis IOT pada Fotovoltaik Monokristalin untuk Catu Daya Alat Insect Light Trap - Vemas Nofriadi; Ibrohim Ibrohim (Indo Publishing, 2026)
Indonesia has significant potential for the utilization of solar energy. However, the efficiency of conventional photovoltaic systems remains limited because most solar panels are installed in fixed positions. This study aims to design and analyze an Internet of Things (IoT)-based Dual-Axis Solar Tracker using monocrystalline photovoltaic panels to power an insect light trap. The research employed a quantitative experimental approach involving system design, prototype implementation, hardware and software integration, and performance testing. This study addresses the gap in previous research by integrating a dual-axis solar tracker, monocrystalline photovoltaic technology, and real-time IoT monitoring into a single system specifically designed to support an insect light trap. The novelty of this research lies in the integration of automatic solar tracking with real-time monitoring of voltage, current, and power through the Blynk platform. The experimental results show that the dual-axis solar tracker operated successfully and achieved a photovoltaic conversion efficiency of 6.98%, which is higher than the 5.15% efficiency of the fixed photovoltaic system. Furthermore, the proposed system produced an average output power of 11.73 W, compared with 8.65 W generated by the fixed solar panel system, representing an improvement in solar energy harvesting of approximately 35.6%.